ChemInform Abstract: A General Approach to Catalytic Alkene Anti‐Markovnikov Hydrofunctionalization Reactions via Acridinium Photoredox Catalysis. Issue 46 (October 2016) - Margrey, Kaila A.; Nicewicz, David A.
Abstract: Review: 44 refs.